Implementation of the 5E Learning Cycle Learning Model Assisted by YouTube to Improve Writing Skills for Observation Report Texts in Class VIII Students of MTsN 2 Buleleng - Elfina Damayanti; I Gede Nurjaya; Kadek Wirahyuni (Lembaga Bale Literasi, 2026)
The results of the study indicate that the application of the Learning Cycle 5E learning model assisted by YouTube can improve students' writing observation report texts. The success criteria in this study were determined by achieving a minimum of 80% learning mastery and positive student responses toward the learning model implementation. The findings showed that students’ writing skills improved in each cycle. In cycle I, the average score of students reached 73.3 with a learning mastery percentage of 70.4%. In cycle II, the average score increased to 84.4 with a learning mastery percentage of 92.6%, indicating that the success criteria had been achieved. In addition, student responses to the implementation of the Learning Cycle 5E learning model assisted by YouTube also increased. In cycle I, the average score of student responses was 25.6, categorized as very positive, and increased in cycle II to 27.3, also categorized as very positive. Thus, the implementation of the Learning Cycle 5E learning model assisted by YouTube has been proven effective in improving the observation report text writing skills of class VIII-C students of MTsN 2 Buleleng.